A multi‐locus approach resolves the phylogenetic relationships of the Simulium asakoae and Simulium ceylonicum species groups in Malaysia: evidence for distinct evolutionary lineages. Issue 3 (13th May 2015) - LOW, V. L.; TAKAOKA, H.; ADLER, P. H.; YA'COB, Z.; NORMA‐RASHID, Y.; CHEN, C. D.; SOFIAN‐AZIRUN, M.
Abstract A multi‐locus approach was used to examine the DNA sequences of 10 nominal species of blackfly in the Simulium subgenus Gomphostilbia (Diptera: Simuliidae) in Malaysia. Molecular data were acquired from partial DNA sequences of the mitochondria‐encoded cytochrome c oxidase subunit I (COI), 12S rRNA and 16S rRNA genes, and the nuclear‐encoded 18S rRNA and 28S rRNA genes. No single gene, nor the concatenated gene set, resolved all species or all relationships. However, all morphologically established species were supported by at least one gene. The multi‐locus sequence analysis revealed two distinct evolutionary lineages, conforming to the morphotaxonomically recognized Simulium asakoae and Simulium ceylonicum species groups.